Toxoplasma gondii Triggers Neutrophil Extracellular Traps Release in Dogs - Wei, Zhengkai; Wang, Zedong; Liu, Xiao; Wang, Chaoqun; Han, Zhen; Wu, Di; Zhang, Yong; Zhang, Xichen; Yang, Zhengtao; Liu, Quan (Frontiers in Cellular and Infection Microbiology, 2020)
Toxoplasma gondii (T. gondii) can cause zoonotic toxoplasmosis worldwide. Neutrophils extracellular traps (NETs) have been known as a novel effector mechanism against T. gondii infection in the innate system of humans, cats and sheep. Dogs are the intermediate host of T. gondii, in which NETs against T. gondii infection remains unclear. Thus, the study aims to examine the effects of T. gondii on NETs release in dogs, and further to investigate the mechanism involving in the process. T. gondii-triggered NETs were analyzed by scanning electron microscopy (SEM) and fluorescence confocal microscopy, and the mechanism of T. gondii-triggered NETs release was determined by using inhibitors and the fluorometric reader. The results showed that T. gondii tachyzoites significantly triggered NETs-like structures, which consisted of DNA decorated with neutrophil elastase (NE) and myeloperoxidase (MPO). Further investigations revealed that reactive oxygen species (ROS)-, NADPH oxidase-, Rac 1- or p38 mitogen-activated protein kinase (MAPK)- signaling pathways were relevant to T. gondii tachyzoites-triggered NETs release. Moreover, zymosan-triggered NETs release was strikingly degraded by T. gondii tachyzoites treatment, indicating that T. gondii may escape from the NETs-based capture strategy. Taken together, promoting NETs release is suggested to limit motility and evade infection of T. gondii in dogs.